STUDENTS' MATHEMATICAL CONNECTION ABILITY IN SOLVING PROBLEMS - Timbul Yuwono; Tatik Retno Murniasih (Universitas Muhammadiyah Metro, 2024)
The purpose of this study is to describe high, mid, and low mathematical abilities in solving mathematics problems of grade VII SMP PGRI 06 Malang in the 2019/2020 academic year. Data analysis techniques were carried out from the results of mathematical connection tests, problem solving tests and interview instruments. The research subjects were 22 students. Researchers took 3 subjects representing high, mid, and low ability students. Researchers used instruments of problem-solving tests and interview guides. Finally, the research concludes that high-ability students do all activities in the indicators of mathematical connection ability in solving problems; mid-ability students do not do all the activities in the indicator of mathematical connection ability in solving problems; Students with low mathematical abilities do not do all activities in the indicator of mathematical connection ability in solving problems. Tujuan dari penelitian ini adalah untuk mendeskripsikan kemampuan matematika tinggi, sedang dan rendah dalam menyelesaikan masalah matematika siswa kelas VII SMP PGRI 06 Malang tahun pelajaran 2019/2020. Teknik analisis data dilakukan dari hasil tes koneksi matematis, tes pemecahan masalah dan instrumen wawancara. Subjek penelitian adalah 22 siswa. Peneliti mengambil 3 subjek yang mewakili siswa berkemampuan tinggi, sedang dan rendah. Peneliti menggunakan instrumen tes pemecahan masalah dan pedoman wawancara. Hasil penelitian  ini bahwa siswa berkemampuan tinggi melakukan semua aktivitas dalam indikator kemampuan koneksi matematis dalam memecahkan masalah; siswa berkemampuan sedang tidak melakukan semua aktivitas pada indikator kemampuan koneksi matematis dalam menyelesaikan masalah; Siswa dengan kemampuan matematis rendah tidak melakukan semua aktivitas pada indikator kemampuan koneksi matematis dalam menyelesaikan masalah.